Local community awareness towards water based activity in Panchor - Abrar, Azrai; Md Sawari, Siti Salwa (2019)
Local community is an important aspect to develop a tourism activity in a rural area. Therefore, local community needs to be acknowledged regarding the tourism in their area the. Thus, this study aims to investigate the local community awareness towards water-based activity in Panchor River. This study focusing on three objectives which are; 1) To investigate local community awareness of water-based activity, 2) To identify the relationship between local community knowledge and local awareness and 3) To identify the relationship between local community attitude and local awareness. This study is quantitative in nature. A total of 30 respondents from Panchor participated in this research. The data was analyzed by using IBM Statistical Package for Social Science (SPSS) version 21 through several analyses such as descriptive analysis, frequency analysis, reliability analysis, Pearson correlation analysis and correlation analysis. The outcomes of this study will show the relationship between knowledge and attitude towards local community awareness, and the relationship analysis show that knowledge and local community awareness have a strong, while the attitude have only positive relationship with local awareness tourism. The first major practical contribution of the study is that it has significant contribution to the local community in Panchor to help them to involve and earn more income through tourism.